Habitus, Capital, and Distinction: Capital Control Strategy Through the Practice of Virtual Commodity Microtransactions in Online Games - Anak Agung Ngurah Agung Suryadipta Wardhana (Institut Seni Indonesia Yogyakarta, 2023)
This research article aims to understand how capital control strategies are carried out by players in online video games through the practice of virtual commodity microtransactions. The research was carried out using a qualitative approach and literature review as a method for presenting the reality related to social interactions in online video games and microtransactions practices. The reality discovered through the literature review process is then analyzed based on the postmodernism perspective of Pierre Bourdieu regarding habitus, economic capital, social capital, symbolic capital, and distinction. The results of the study show that online video game players practice virtual commodity microtransactions as a capital control strategy. The players also convert capital forms according to their tastes and desires. Judgment of tastes in the context of online video games arises from the formation of virtual social classes based on capital ownership among the players. The practice of microtransactions then becomes a capital control strategy for players to climb the virtual social hierarchy or maintain their position.